Artificial Groundwater Recharge Zones Mapping using Remote Sensing and GIS for Sub-Watersheds of Krishna Basin - Jeevan Madapala; Jahnavi Puppala (International Journal of Engineering and Management Research, 2022)
The exacerbated exploitation of groundwater resources has led to an alarming decrease in groundwater levels. It is necessary to identify areas that allow for efficient recharge so that implementation of artificial groundwater recharge can be conducted in such areas with better efficiency. This study maps zones with their varying degrees of affinity for groundwater recharge in two of the sub-watersheds of the Krishna Basin. The factors affecting the potential of groundwater recharge were determined and then thematic maps for each factor were generated in ArcGIS 10.8. Remote sensing data from sources like ‘Bhuvan’ and ‘Bhukosh’ were used for the generation of the thematic layers. The Analytic Hierarchy Process (AHP) was used while deciding the relative and subsequently overall importance of each layer. The weights derived from the AHP were applied to the thematic layers and the mapping of zones for artificial groundwater recharge was done.